2016
DOI: 10.1117/12.2229428
|View full text |Cite
|
Sign up to set email alerts
|

Progress and challenges in electrically pumped GaN-based VCSELs

Abstract: The Vertical-Cavity Surface-Emitting Laser (VCSEL) is an established optical source in short-distance optical communication links, computer mice and tailored infrared power heating systems. Its low power consumption, easy integration into two-dimensional arrays, and low-cost manufacturing also make this type of semiconductor laser suitable for application in areas such as high-resolution printing, medical applications, and general lighting. However, these applications require emission wavelengths in the blue-U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 144 publications
(158 reference statements)
0
13
0
Order By: Relevance
“…In recent years, several academic and industrial research groups have demonstrated electrically pumped GaN-based VCSELs [3]- [11]. However, the performance of GaN-based VCSELs is still not good enough and challenges are necessary in such as achieving high-reflectivity mirrors, efficient lateral current spreading and lateral optical confinement (LOC) [12]. Further improvements in GaNbased VCSELs are required toward applications.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, several academic and industrial research groups have demonstrated electrically pumped GaN-based VCSELs [3]- [11]. However, the performance of GaN-based VCSELs is still not good enough and challenges are necessary in such as achieving high-reflectivity mirrors, efficient lateral current spreading and lateral optical confinement (LOC) [12]. Further improvements in GaNbased VCSELs are required toward applications.…”
Section: Introductionmentioning
confidence: 99%
“…Among those methods, Al x Ga 1−x N electron blocking layer (EBL) is usually placed between the active region and p-GaN layer, since it provides a higher energy barrier in the conduction band between quantum wells (QWs) and the p-layers. The higher energy barrier in the conduction band contributes to the confinement of the electrons in the active region, so stronger output power can be achieved [15]. However, the very commonly used Al x Ga 1−x N EBL sometimes cannot efficiently reduce electron leakage due to the polarization charge in that layer, which decreases the barrier height for electron transport [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…sensing and optical communication. However, III-nitride based VCSELs with emission wavelengths in the UV and visible, which could find applications in pico projectors, head-up and near-eye displays, biomedicine, and visible-light communication [1], [2], are still not commercially available. Several research groups have reported lasing of electrically injected III-nitride VCSELs [3]- [12] but there is still a need to reach higher output powers, lower threshold currents and improved thermal stability.…”
Section: Introductionmentioning
confidence: 99%